Cross-Connected Source Multilevel Inverter for Active Power Filtering Using Unified Constant-Frequency Integration Control - Hairol Jaffar; Naziha Ahmad Azli (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper proposes an Active Power Filter (APF) system which utilizes a five-level nonconventional Cross-Connected Source Multilevel Inverter (CCSMI) with a modified Unified Constant-Frequency Integration (UCI) control. The CCSMI consists of six power switches which can produce five output voltage levels. With the use of the CCSMI, the parts count is reduced with equivalent or better performance compared to the use of conventional multilevel inverters. The capability of the proposed system is tested using three types of nonlinear loads with different characteristics. The APF system is simulated under steady-state condition using MATLAB/Simulink. The results obtained show improvement in the supply current Total Harmonic Distortion (THD) with room for enhancement, using the proposed APF system.